Pemanfaatan Cangkang Udang Sebagai Biokoagulan Untuk Menurunkan Limbah Cucian Mobil di Kota Bengkulu - Pratama, Muhammad Ryan; Martono, Agus; Santoso, Urip; Brata, Bieng; Yurike; Kurnia, Agung (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
Car wash services in Bengkulu City are increasing along with the increasing number of motorized vehicles. This also increases car wash wastewater which has an impact on wastewater pollution. For this reason, this study aims to test the coagulant production process from shrimp shell powder. A series of tests will be carried out to obtain results in the form of the effectiveness of shrimp shells as a coagulant to reduce COD, TSS, Phosphate, and pH values. The results of this study indicate that the average COD, phosphate TSS degree of water acidity (pH) of car wash waste is in accordance with the quality standards according to the Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014. It can be concluded as follows Shrimp shell as a coagulant can reduce COD values, TSS, phosphate, degree of water acidity (pH) in car wash waste. Keywords: Car Wash Wastewater, Laundry Service, Shrimp Shells